Liquid Membrane Technology For Precious Metals Recovery From Industrial Waste - Othman, Norasikin; Goto, Masahiro; Mat, Hanapi (2004)
A basic principle of the liquid membrane technology is reviewed by highlighting some interesting features of the system over other processes especially for metal separation and recovery from industrial wastes. Some of commercial liquid membrane extraction processes of precious metals are presented as examples of potential applications of the system. The advantages and drawbacks of the liquid membrane technology and the future research direction are also included.